2016
DOI: 10.3747/pdi.2014.00247
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cognitive Impairment among Peritoneal Dialysis Patients, Impact on Peritonitis and Role of Assisted Dialysis

Abstract: Cognitive impairment is common among local PD patients. Even with CI, peritonitis rate in self-care PD with adequate training is similar to CI patients on assisted PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 19 publications
3
37
1
Order By: Relevance
“…12 Additionally, a higher number of comorbidity was negatively associated with nonadherence fluid intake among Chinese hemodialysis patients. 39 Similar to our study, some studies failed to detect any impact of gender, education, or employment on nonadherence. 16,38 This study has several strengths, including it being the first local study to estimate the prevalence and the associations of psychosocial predictors with nonadherence, using multiple validated psychosocial outcomes, in a multicenter experience, with adjustments for relevant demographic and clinical characteristics.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…12 Additionally, a higher number of comorbidity was negatively associated with nonadherence fluid intake among Chinese hemodialysis patients. 39 Similar to our study, some studies failed to detect any impact of gender, education, or employment on nonadherence. 16,38 This study has several strengths, including it being the first local study to estimate the prevalence and the associations of psychosocial predictors with nonadherence, using multiple validated psychosocial outcomes, in a multicenter experience, with adjustments for relevant demographic and clinical characteristics.…”
Section: Resultssupporting
confidence: 57%
“…37,38 However, our rate of cognitive impairment was higher than reported by other studies. 6,39 Cognitive impairment in our patients was strongly associated with older age (data not shown). Similarly, aging in dialysis patients and the presence of cerebrovascular diseases were shown to play a major role in the pathophysiology of cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Through more specific screening in Hong‐Kong patients commencing PD, the administration of the Montreal Cognitive Assessment (MOCA) tool during PD training identified NCI in 29%, with a 4‐fold increase among those patients over 65 years. In addition to age, terminating education below secondary level and a history of hypertension or peripheral vascular disease was associated with the detection of NCI . Cross‐sectional analysis comparing a formal neuropsychological test battery in English‐speaking patients established on PD, HD or healthy volunteers found an odds ratio for NCI compared to control of 2.58 and 3.1 for PD and HD, respectively, against a control NCI rate significantly higher than commonly reported .…”
Section: The Impact Of Dialysis Modalitymentioning
confidence: 90%
“…Data from home‐based dialysis therapies, where clinically obvious NCI is typically a barrier to entry and concerns regarding independence, technique and patient survival are magnified, is much more limited. A single 1‐year prospective cohort study of 114 PD patients found those with confirmed NCI report significantly higher requirements for assistance with dialytic and day‐to‐day care, while demonstrating no difference in terms of PD‐associated peritonitis rates . The risk of developing NCI once established on a home‐based therapy, or the hypothesis that this dialysis choice might be in some way protective, is challenged by selection biases inherent to home‐dialysis and has not been explored.…”
Section: Implications and Perspectivesmentioning
confidence: 99%
“…Another solution is to try a multisensory approach, using photographs of the bagexchange procedure or the provision of simple, step-by-step instructions on audiotape (21). A study on the prevalence of cognitive impairment (CI) in PD patients using Montreal Cognitive Assessment found that CI was not a significant independent risk factor for PD-related peritonitis among self-care PD patients with adequate training (22).…”
Section: Learning Plans and Evaluationmentioning
confidence: 99%